The Impact of Risk Management Implementation on Healthcare Projects: An Applied Study on Hospitals in Jeddah (The International Journal for Scientific Research, 2024)
This study aims to evaluate the impact of implementing risk management systems on healthcare quality in hospitals in Jeddah. Given the increasing challenges facing the healthcare sector, the study includes an analysis of the effects of risk management on patient safety, healthcare service quality, and operational efficiency in hospitals. The study employed a descriptive-analytical method and used both quantitative and qualitative data collection tools, including surveys and interviews with 200 participants from public and private hospitals in Jeddah. The results indicate that implementing risk management systems has a significant positive impact on improving healthcare quality and patient safety. About 60% of participants reported an improvement in healthcare quality, and 50% noted an improvement in patient safety following the implementation of risk management systems. These findings align with previous studies that emphasized the importance of risk management in reducing medical errors and enhancing healthcare service quality. Additionally, the study identified several challenges to effective risk management implementation, including a lack of financial resources, insufficient training, and resistance to change among medical and administrative staff. These challenges highlight the need to enhance training programs and awareness to ensure a broader and more comprehensive understanding of risk management concepts, as well as to improve administrative support and provide necessary resources. The study recommends several actions to improve risk management systems in Jeddah hospitals, including increasing training and awareness programs, enhancing administrative support, utilizing modern technology for data analysis and risk management, and regularly updating policies and procedures to ensure alignment with modern standards.
Keywords: Risk Management; Healthcare Quality; Patient Safety; Jeddah Hospitals; Operational Efficiency; Reducing Medical Errors; Training and Administrative Support; Health Information Technology